Soybean Yield and Nutritional Status Response to Nitrogen Sources and Rates of Foliar Fertilization. (1st March 2017) - Moreira, A.; Moraes, L. A. C.; Schroth, G.; Becker, F. J.; Mandarino, J. M. G.
Abstract : Core Ideas: In high‐yielding conditions, biological nitrogen fixation and soil total N may not be sufficient to sustain N uptake rates during soybean seed‐filling period to meet the seed N demand required to reach the maximum attainable seed yield. Foliar N fertilization in R3 to R4 growth stages may be used to increase N supply during the final reproductive cycle of plant. The importance on nutrients application, in special N, in crop production has increased in recent years in tropical and subtropical conditions in Brazil because of intensive cultivation (soybean–wheat, soybean–corn, and soybean–cotton), use of high yielding cultivars, and increasing the cost of production. Nitrogen sources (urea, ammonium nitrate, potassium nitrate, calcium nitrate, and ammonium sulfate) and rates (0, 5, and 10 kg ha −1 ) have different responses and efficiency index in seed yield, when N foliar applied on soybean leaves at the R3 to R4 growth stages. The response of soybean [ Glycine max (L.) Merr.] to foliar N application during pod formation has been inconsistent. The objective of this study over three growing seasons was to evaluate the effects of foliar N sources and rates of application on yield, nutritional status, and yield components of soybean. The treatments consisted of five sources [NO3 NH4, CaNO3, KNO3, urea‐[CO(NH2 )2 ], and (NH4 )2 SO4 ], two N rates (5 and 10 kg N ha −1 ), applied at the beginning pod growth stage, and a control (no‐N fertilization). Foliar N generally increased the seed yield, irrespective of the N source and analysis pooled over three growing seasons showed an average seed yield increase of 5.0% (211 kg ha −1 ) and 6.1% (259 kg ha −1 ) for the 5 and 10 kg N ha −1 over control, respectively. Neither N rate nor source affected seed size, protein, oil, and nutritional status of leaves or seed. Nitrogen rate affected N use efficiency, but results varied with N sources. These data suggest that foliar N application may increase yield of soybean under certain environmental conditions.